Pengaruh Keamanan, Convenience Risk, dan Persepsi Risiko Produk terhadap Minat Beli Online pada Situs Jual Beli Shopee - Gendis Chintia Luna; Eka Sudarusman (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
Online transactions are buying and selling through internet media, so buyers and sellers do not meet face to face. The easier it is to make transactions, it will also affect people’s views, this is inseparable from the many cases of online crimes such as credit card hackers, illegal transactions and fraud. This research seeks to find out the public’s view of online transactions, in terms of security, risk, and also the perception of product risk on online buying interest. This research was conducted in Yogyakarta to analyze the effect of security, convenience risk, and perceived product risk on online purchase intention on the Shopee buying and selling site. Based on the results of the analysis and discussion, the conclusions of this study are as follows: Security (X1) has no effect on online buying interest. Convenience risk (X2) has a positive and significant effect on online buying interest. Perceived Product Risk (X3) has a positive and significant effect on online buying interest.